Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have to solve : $$0 = \ln(x) - \ln(1-x).$$

I did:

$0 = \ln(x) - \ln(1-x) \implies e^0 = e^{\ln(x)} - e^{\ln(1-x)} \implies 1 = x - (1-x) \implies 2 = 2x \implies x=1 $

The solution should be $x=\frac{1}{2}$

Where is my fault ? :(

share|cite|improve this question
up vote 10 down vote accepted

After you take '$e$' of both sides you do indeed arrive at $$ e^0 = e^{ \ln x - \ln(1-x) } $$ because of the general property that $ a=b \implies e^a=e^b$. However, you then tried to use a false rule, that $e^{a-b} = e^{a} - e^{b} $. If you recall your index laws, you'll remember that the proper rule is $$ e^{a-b} = \frac{e^a}{e^b} .$$

share|cite|improve this answer

The problem is that if you take exponentials of both sides, you should get $$e^0 = e^{\ln(x) - \ln(1-x)}.$$ But $$e^{\ln(x) - \ln(1-x)} \neq e^{\ln(x)} - e^{\ln(1-x)}.$$ So your first step is incorrect.

Simplest thing is to first go from $0 = \ln(x) - \ln(1-x)$ to $\ln(1-x) = \ln(x)$ and then take the exponentials.

Alternatively, from $$ e^0 = e^{\ln (x) - \ln(1-x)}$$ you can use the fact that $e^{a-b} = \frac{e^a}{e^b}$ to get $$ 1 = \frac{e^{\ln(x)}}{e^{\ln(1-x)}},$$ and proceed from there.

P.S. Please don't use [homework] as the only tag in your post.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.